Female OFWs in the national cultural imaginary embedded discourses in popular mainstream of OFW films - Tan, Katrina Ross Andal 1984- (2011.)
"The study aims to determine how OFW films from different periods of history embed discourses on overseas work. To answer this entails an analysis of the discourses and generic elements of OFW films from different decades. Part of the objective also is to identify changes in narrative and aesthetic elements in relation to the embedded discourses. Using Foucault's theory on discourse and Altman's approach on genre criticism, I applied textual analysis in analyzing selected popular mainstream OFW films namely, Miss X (1980), Merika (1984), Flor Contemplacion Story (1995), Anak (2001) and Caregiver (2008). Prior to the analysis, I presented a historiography of the State's labor export policies in relation to the bureaucratization of the film industry and a listing of OFW films to map out their respective emergence. Based on the analyses, OFW films embed discourses through filmic elements that were identified to have changed over time, bringing a gradual change in generic conventions. These films registered gradual changes in characterization, plot structure, visual representation, and deployment of major movies stars. These generic changes, in turn, articulate a change in discourse in OFW films. While earlier OFW films have a discourse on overseas work that echoes the common notion that it is necessary and that it is the only opportunity the OFW characters have to provide for their family, they tend to be skeptic and even critical of the government for lack of protection for OFWs. On the other hand, more recent popular mainstream OFW films, although they contain indirect criticisms regarding the logic of overseas work, tend to be complicit with the State in encouraging Filipinos to become OFWs that is made more compelling with the use of major movie stars as the central OFW characters in the film. This complicity is cemented further through an increasing regulation of filmic discourses, particularly relating to overseas work, as a result of the State policies affecting the film industry."
Vita.
Thesis (M.A. Media Studies (Film)--University of the Philippines.
Keywords: Alien labor in motion pictures; Women in motion pictures; Popular culture